Les monuments inachevés de l’époque romaine au Liban. Une approche analytique du phénomène - Kahwagi-Janho, Hany (Études et Travaux, 2024)
During the Roman era, Lebanon experienced significant economic and urban growth. Thus, the Lebanese territory was marked by the development of dozens of largescale architectural projects. This evolution took two main aspects: on the one hand, several already existing buildings underwent an ‘upgrade’ in order to conform them to the newly introduced ‘canonical’ Roman models. On the other hand, several new projects emerged both in coastal towns and in rural areas. However, many, if not most, of these monuments remained unfinished. These unfinished states vary between the cancellation of large parts of the original construction program and the incompleteness of decorative details such as the entablatures of several others. Thus, through this article, we will discuss several examples showing the various aspects and levels of incompleteness of these monuments as well as the potential hypotheses linked to this phenomenon which seems to have become widespread during this period.